2017
DOI: 10.14814/phy2.13342
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning does not alter muscle sympathetic responses to static handgrip and metaboreflex activation in young healthy men

Abstract: Ischemic preconditioning (IPC) has been hypothesized to elicit ergogenic effects by reducing feedback from metabolically sensitive group III/IV muscle afferents during exercise. If so, reflex efferent neural outflow should be attenuated. We investigated the effects of IPC on muscle sympathetic nerve activity (MSNA) during static handgrip (SHG) and used post‐exercise circulatory occlusion (PECO) to isolate for the muscle metaboreflex. Thirty‐seven healthy men (age: 24 ± 5 years [mean ± SD]) were randomized to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 50 publications
4
29
2
Order By: Relevance
“…Mulliri et al ( 2016 ) reported IPC did not change central and peripheral hemodynamic parameters during exercise, but IPC decreased mean arterial pressure during post-exercise circulatory occlusion due to a venous return-induced reduction of stroke volume and cardiac output. Of note, however, Incognito et al ( 2017 ) and Mulliri et al ( 2016 ) did not provide enough data to interpret the IPC effect under normal free flow recovery from exercise, like we did in the present study. In addition, cardiovascular responses to handgrip exercise are very different from those provoked by dynamic exercise involving large muscle mass (Lewis et al, 1985 ).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Mulliri et al ( 2016 ) reported IPC did not change central and peripheral hemodynamic parameters during exercise, but IPC decreased mean arterial pressure during post-exercise circulatory occlusion due to a venous return-induced reduction of stroke volume and cardiac output. Of note, however, Incognito et al ( 2017 ) and Mulliri et al ( 2016 ) did not provide enough data to interpret the IPC effect under normal free flow recovery from exercise, like we did in the present study. In addition, cardiovascular responses to handgrip exercise are very different from those provoked by dynamic exercise involving large muscle mass (Lewis et al, 1985 ).…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast, in our study HR surpassed 180 bpm. Therefore, methodological dissimilarities preclude comparison of the IPC effect on post-exercise cardiovascular parameters between former studies (Mulliri et al, 2016 ; Incognito et al, 2017 ) and the present one.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Lower SNA has been observed following limb ischemia reperfusion injury preceded by IPC using the gold standard microneurography ( Lambert et al, 2016 ). However, it has recently been reported that no change in SNA was present during static handgrip at 30% MVC, following IPC versus a SHAM condition ( Incognito et al, 2017 ). Based on the available evidence, we cannot currently elucidate this mechanism.…”
Section: Discussionmentioning
confidence: 99%